Redox Mechanisms of AVS022, an Oriental Polyherbal Formula, and Its Component Herbs in Protection against Induction of Matrix Metalloproteinase-1 in UVA-Irradiated Keratinocyte HaCaT Cells. (19th September 2013) - Pluemsamran, Thanyawan; Tripatara, Pinpat; Phadungrakwittaya, Rattana; Akarasereenont, Pravit; Laohapand, Tawee; Panich, Uraiwan
Abstract : Ayurved Siriraj HaRak (AVS022) formula has been used for topical remedy of dermatologic disorders. Oxidative stress induced by ultraviolet (UV) A irradiation could be implicated in photoaged skin through triggering matrix metalloproteinase-1 (MMP-1). We, therefore, explored the antioxidant mechanisms by which AVS022 formulation and its individual components protected against UVA-dependent MMP-1 upregulation in keratinocyte HaCaT cells. TLC analysis revealed the presence of multiple phenolics including gallic acid (GA) in the AVS022 extracts. We demonstrated that pretreatment with the whole formula and individual herbal components except T. triandra protected against increased MMP-1 activity in irradiated HaCaT cells. Moreover, all herbal extracts and GA, used as the reference compound, were able to reverse cytotoxicity, oxidant production, glutathione (GSH) loss, and inactivation of catalase and glutathione peroxidase (GPx). F. racemosa was observed to yield the strongest abilities to abolish UVA-mediated induction of MMP-1 and impairment of antioxidant defenses including GSH and catalase. Our observations suggest that upregulation of endogenous antioxidants could be the mechanisms by which AVS022 and its herbal components suppressed UVA-stimulated MMP-1 in HaCaT cells. In addition, pharmacological actions of AVS022 formula may be attributed to the antioxidant potential of its components, in particular F. racemosa, and several phenolics including GA.